Deciphering the psychological tapestry of FGIDs: unveiling the impact of negative affect, rumination, and expression suppression - Xin-Xin Ma; Zheng-Hua Xiao; Wei Chen; Shou-Ying Zhao (BMC Public Health)
Abstract Background Functional Gastrointestinal Disorders (FGIDs) constitute a group of psychosomatic diseases characterized primarily by disruptions in the functioning of the digestive system, profoundly impacting the lives of affected individuals. Objective This study aims to investigate the influence of negative affect (NA) on the gastrointestinal symptoms of FGID patients, as well as the mediating role of rumination and the regulatory effects of expression suppression (ES) as an emotional regulation strategy. Methods A survey was conducted on 1000 patients (403M, 597F) with gastrointestinal disorders at a tertiary hospital using the negative affect subscale from the DS-14 (Type D Personality Scale), the Gastrointestinal Symptom Rating Scale (GSRS), the Rumination Response Scale (RRS), and the expression suppression subscale from the Gross-John Emotion Regulation Strategy. Results Negative affect positively predicts FGIDs, with rumination mediating the relationship between NA and FGIDs. The emotional regulation strategy of expression suppression moderates the positive relationship between NA and rumination and the mediating effect of rumination. Conclusion NA exacerbates symptoms of FGIDs in individuals, and rumination further amplifies this effect, with the mediating influence evident across both high and low ES emotion regulation strategy groups.